1990
DOI: 10.1111/j.1365-2621.1990.tb05203.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biochemical and Bacteriological Quality of Grass Prawn during Transportation by Icing and Oxygenating

Abstract: Live grass prawns (Penaercs monodon) were iced or oxygenated in cold water and examined for changes in biochemical and bacterial quality during transportation from the farm to the processing plant. The biochemical quality of oxygenated prawns as assessed by volatile base nitrogen (VB-N), extractable nitrogen (AA-N), VB-N/AA-N ratio, K-value, water-holding capacity and sensory results, was superior to that of iced prawn. No distinct differences in inosine 5'-monophosphate (IMP) ratio, nucleotides profile and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…These results agree with those mentioned by Chen et al (1990) and Jeyasekaran et al (2006) for fresh and iced shrimps. The pH range in this study varied from 7.39 to 7.76 in thawed frozen shrimps and from 7.01 to 7.35 in marinated one.…”
Section: -Weight Loss and Phsupporting
confidence: 93%
“…These results agree with those mentioned by Chen et al (1990) and Jeyasekaran et al (2006) for fresh and iced shrimps. The pH range in this study varied from 7.39 to 7.76 in thawed frozen shrimps and from 7.01 to 7.35 in marinated one.…”
Section: -Weight Loss and Phsupporting
confidence: 93%
“…Their presence in high numbers (>10 4 g -1 ) in ready-toeat foods indicates that an unacceptable level of contamination has occurred. Consistent with the present study, Chen et al [38] while analyzing bacteriological quality of shrimp, did not find Salmonella and Antony et al [35] also observed similar findings. In Thailand, Dalsgaard et al [39] also reported that Salmonella was not detected from shrimps.…”
Section: Discussionsupporting
confidence: 81%
“…This could explain why IMP was higher in infected animals (Gornik et al 2010). In crustaceans, IMP has been described as a marker of muscular fatigue and an indicator of a compromised physiological state due to extreme stresses (Chen et al 1990, Paterson 1993. The fact that this nucleotide was higher in symptomatic Nephrops norvegicus after capture is therefore consistent with the finding that at advanced stages of infection this parasite totally depletes the energy stores of the host, inducing a state of physiological collapse (Stentiford et al 2000).…”
Section: Discussionsupporting
confidence: 63%